The Influence of Visual Presentations and Online Reviews on Hotel Booking Intention on the Tiket.Com Application (Case Study: Tiket.Com Application Users) - Wardianti, Shiffa Intania; Hidayah, Riski Taufik (Indonesian Academy of Social and Religious Research (IASRR), 2023)
Tiket.com is an Online Travel Agent (OTA) that provides online hotel bookings. This study aims to analyze the effect of visual presentation and online reviews on hotel booking intention on the Tiket.com application. This research integrates visual presentation and online reviews with the Technology Acceptance Model (TAM). The variables tested consist of Visual presentation, Perceived Ease of Use, and Online review as independent variables, Perceived Usefulness as a moderating variable, and Booking Intention as the dependent variable. The type of research is quantitative with a cross-sectional design and the research subjects are users of the Tiket.com application. Data was collected by distributing questionnaires to 119 respondents. The research hypothesis was tested using the Partial Least Squares Structural Equation Model (PLS-SEM) analysis technique. Based on the results of the hypothesis, H1, H3, and H8 are not in line with previous thinking because they do not positively influence buying interest in the tiket.com application. tiket.com applications should update booking features, and more attractive colors, update the system, reduce addsens, and update a more modern look.